2018
DOI: 10.1142/s0217751x18502184
|View full text |Cite
|
Sign up to set email alerts
|

q-deformed Einstein equations from entropic force

Abstract: In this study, we investigate the influences of fermionic q-deformation on the Einstein equations by taking into account of Verlinde's entropic gravity approach and Strominger's proposal on quantum black holes. According to Verlinde's proposal, gravity is interpreted as an entropic force. Moreover, Strominger's suggetion claims that extremal black holes obey deformed statistics instead of the standard Bose or Fermi statistics. Inspired by Verlinde's and Strominger's suggestions, we represent some thermostatist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…For this purpose, we considered three different deformed gas models in the high-temperature limits. First two models [25,26] are related one parameter q-deformed fermion and fermion-boson gas system, respectively, and the third one [24] corresponds to two-parameters (q, p)-deformed of fermion gas system. We wrote the temperature function in a compact form depending on these models in Eq.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For this purpose, we considered three different deformed gas models in the high-temperature limits. First two models [25,26] are related one parameter q-deformed fermion and fermion-boson gas system, respectively, and the third one [24] corresponds to two-parameters (q, p)-deformed of fermion gas system. We wrote the temperature function in a compact form depending on these models in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the study [23] showed us that the deformed Einstein equation can be derived by using deformed statistics rather than standard one to describe gravitational behaviors of the quantum black holes in the framework of the entropic gravity suggestion. From this motivation, the different deformation of Einstein's field equations have been obtained by considering the extremal quantum black holes as q-deformed fermions [25], q-deformed bosons and fermions [26], and (q, p)-deformed fermions [24] for the high-temperature limits. In this section, we briefly review the useful results of these three models.…”
Section: One and Two-parameters Deformed Entropic Gravitymentioning
confidence: 99%
See 3 more Smart Citations